Getting Back to the Source: A New Approach to Measuring Ex Ante Litigation Risk Using Plaintiff-Lawyer Views of SEC Filings - Kartapanis, Antonis; Yust, Christopher G. (Journal of Financial and Quantitative Analysis, 2024)
Abstract This study introduces a new measure of ex ante litigation risk using scrutiny of SEC filings by the source of securities litigation (plaintiffs’ lawyers) to reduce measurement error, relative to existing measures. We show that plaintiff-lawyer views proxy for the largely unobservable factors that make firms more likely to face litigation risk. Lagged views precede the public bad news revelation that triggers litigation and predicts future realized litigation risk (i.e., securities class actions filings and plaintiff-lawyer investigations) and stock market outcomes. Finally, we provide new insights into the plaintiff-lawyer case selection process that otherwise cannot be observed.